Thermal Comfort Level Analysis to Support Energy Efficiency Based on Building Information Modeling (BIM) (Case Study of Fajar University Postgraduate Building) - Wahyuningsih, Sri; Gusty, Sri; Chaerul, Muhammad (Universitas Ibn Khaldun Bogor, 2025)
Indonesia faces significant challenges regarding energy consumption in the building sector, which continues to rise alongside urbanization and economic growth. Energy use in commercial buildings, particularly office and educational facilities, significantly contributes to the national total energy consumption, with HVAC (Heating, Ventilation, and Air Conditioning) systems being a major component of building energy consumption. By modeling HVAC systems, natural lighting, and thermal insulation, Building Information Modeling (BIM) can help optimize energy usage and reduce operational costs in buildings. However, despite the proven benefits of BIM in energy analysis and thermal comfort, challenges remain in its implementation. Many construction projects still rely on traditional methods that are less effective in integrating data and analysis. Additionally, a lack of understanding about BIM usage among construction professionals also hinders the achievement of optimal energy efficiency.